REPOSISI STRAGTEGI PENTAHELIX UNTUK PARIWISATA DESA BATUJAJAR BARAT: REPOSISI STRAGTEGI PENTAHELIX UNTUK PARIWISATA DESA BATUJAJAR BARAT - Ahmad Dananjaya (Jurnal Perencanaan dan Pengembangan Kebijakan, 2026)
The development of tourism villages through the Pentahelix collaborative model has become a leading strategy in rural planning. However, its implementation often faces challenges in achieving synergy among actors, leading to stagnation. This study aims to analyze the effectiveness of the current Pentahelix model and to formulate a repositioning strategy to accelerate tourism development in West Batujajar Village, West Bandung Regency.This study employed a mixed-methods approach with an explanatory sequential design, involving a survey of 400 household heads and in-depth interviews with key actors from the Government, Academia, Business, Community, and Media sectors. Quantitative data were analyzed using descriptive statistics, index analysis, and a quantified SWOT analysis, while qualitative data were analyzed thematically The findings reveal a significant imbalance of roles: the Government (G) remains dominant in the planning stage, while the roles of the Business (B) and Academic (A) sectors are minimal. Community (C) involvement tends to be reactive and unorganized, and the Media's (M) role as a promotional accelerator has not been optimized. This gap impedes the transformation of local potential into competitive tourism products.Based on these findings, a strategic repositioning model is proposed, emphasizing the strengthening of coordination nodes, a clear division of roles, and a digital collaboration platform. This model is expected to serve as a guide for re-synergizing the actors and achieving sustainable tourism in West Batujajar Village.